CORRELATION BETWEEN HER2 AND EBV EXPRESSION IN GASTRIC CARCINOMA - Ognjenovic, Ljubomir; Sumkovski, Aleksandar; Trajkovski, Gjorgi; Bushinovska, Jasna; Hadzi-Manchev, Dragan; Dzambaz, Darko (Journal of Morphological Sciences, 2020)
The understanding of the etiopathogenesis and the molecular basis of gastric carcinoma will facilitate the development of novel molecular target therapies, which interfere with different signal cascades involved in cellular proliferation, differentiation and survival.The aim of this paper was to determine the correlation between HER2 and EBV expression in patients with gastric carcinomas.   Eighty patients with gastric carcinoma surgically treated were included in the study. Data of HER2 protein expression were obtained from the archive histopathological reports of the Institute of Pathology in Skopje. For detection of EBV, immunostainings were performed on tumor tissue and the peripheral nontumor gastric mucosa.The results of this study confirmed significant association between HER2 and EBV expression (p=0.041). The value of the Spearman correlation coefficient (R = - 0.258) indicated a negative, indirect connection of HER2 and EBV expression, that was confirmed as statistically significant (p = 0.02 levels). The intensity of HER2 expression in gastric carcinomas was significantly associated with EBV expression.  Key words:gastric carcinoma, HER2, EBV, immunohistochemistry.